2013
DOI: 10.3233/ais-130199
|View full text |Cite
|
Sign up to set email alerts
|

Mobile application usage prediction through context-based learning

Abstract: The purchase and download of new applications on all types of smartphones and tablet computers has become increasingly popular. On each mobile device, many applications are installed, often resulting in crowded icon-based interfaces. In this paper, we present a framework for the prediction of a user's future mobile application usage behavior. On the mobile device, the framework continuously monitors the user's previous use of applications together with several context parameters such as speed and location. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In the field of ubiquitous computing, smartphone instrumentation has enabled better understanding of users' interaction with these devices in specific contexts. For example, they have increased our understanding of how people use applications [3,22] and smartphone networks [23], and allowed us to predict which application is relevant to the current context [35,50], and to detect the most opportune moments to deliver information to users [32]. More related to our work, in the area of health and wellbeing, the widespread availability of smartphones in today's young adult population has prompted research that leverages the embedded sensors in smartphones to study human behavior.…”
Section: Smartphone-based Behavior Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of ubiquitous computing, smartphone instrumentation has enabled better understanding of users' interaction with these devices in specific contexts. For example, they have increased our understanding of how people use applications [3,22] and smartphone networks [23], and allowed us to predict which application is relevant to the current context [35,50], and to detect the most opportune moments to deliver information to users [32]. More related to our work, in the area of health and wellbeing, the widespread availability of smartphones in today's young adult population has prompted research that leverages the embedded sensors in smartphones to study human behavior.…”
Section: Smartphone-based Behavior Modelingmentioning
confidence: 99%
“…(a) ESM reports across the participants (n=38) including excluded participants(31)(32)(33)(34)(35)(36)(37)(38) (b) Drinking reports per each participant (n=30): x-axis refers to days during the study (max=28 days), y-axis refers to the number of standard alcohol drinks consumed ESM reports of drinking episodes for each participant.…”
mentioning
confidence: 99%
“…Tu et al [61] measured the uniqueness of mobile app usage behavior considering spatial and temporal context information. Other works [20,24,32,35,55] focused more on the prediction of app usage by studying how to predict which apps users are likely to install or visit. Xu et al [64] identified traffic from distinct marketplace apps and presented statistic results on their spatio-temporal prevalence and correlation.…”
Section: App Usage Modelingmentioning
confidence: 99%
“…Leroux et al developed a mobile framework that creates context profiles by monitoring application use, day of week, and the user's speed and location [18]. Although using artificially created data, the resulting profiles match real life situations, such as "at work" or "commuting," and can be used to infer a set of applications the user is likely to use.…”
Section: Modelling and Predictionmentioning
confidence: 99%